Siblings’ Dispute over Parents’ Transfer: Malaysian Case - KAMARUDIN, Mohd Khairy; MUHAMAD, Nasrul Hisyam Nor (Journal of Advanced Research in Law and Economics, 2018)
The main objective of this work is to examine disputes among children over parents’ transfer problem. This study utilizes qualitative approach in which semi-structured interviews were conducted with ten Land Office Officers. Data is coded to identify themes that contribute to this issue. Later, identified themes are then linked to develop a conceptual framework that explains the disputes among siblings over parents’ transfer. The result discovers two main themes; ‘Siblings do not get the transfer’ and ‘Transferred secretly’ that reflect the siblings’ dispute over parents’ transfer. There are three sub-themes which are ‘Factor(s)’, ‘Impact(s)’ and ‘Solution(s)’ which explain potential factors, impacts and solution for each theme.